Outcome measures for children with speech sound disorder: an umbrella review protocol. Issue 2 (16th February 2023) - Harding, Sam; Burr, Sam; Cleland, Joanne; Stringer, Helen; Wren, Yvonne
Abstract : Introduction: Speech sound disorder (SSD) describes a 'persistent difficulty with speech sound production that interferes with speech intelligibility or prevents verbal communication'. There is a need to establish which care pathways are most effective and efficient for children with SSD. Comparison of care pathways requires clearly defined, evidence-based interventions and agreement on how to measure the outcomes. At present, no list of assessments, interventions or outcomes exists. The objective of this paper is to provide a rigorous and detailed protocol for an umbrella review of assessments, interventions and outcomes that target SSD in children. The protocol details the development of a search strategy and trial of an extraction tool. Methods and analyses: The umbrella review has been registered with PROSPERO (CRD42022316284). Papers included can use a review methodology of any sort but must include children of any age, with an SSD of unknown origin. In accordance with the Joanna Briggs Institute scoping review methods guidelines, an initial search of the Ovid Emcare and Ovid Medline databases was conducted. Following this, a final search strategy for these databases were produced. A draft extraction form was developed. Ethics and dissemination: Ethical approval is not needed for an umbrella review protocol. Following the systematic development of an initial search strategy and extraction form, an umbrella review of this topic can take place. Dissemination of findings will be through peer-reviewed publications, social media, and patient and public engagement.